Patterns and Practices of Sign-Form Variation: Selected Examples of the qjs Logogram from the Fifth to Nineteenth Dynasties - Miller, Jordan Scott (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
A survey of the forms and distribution of the hieroglyphic logogram for the town of Qis ( qjs ). A typology of sign-forms is proposed on the basis of sign lists and selected examples from the Fifth to Nineteenth Dynasties. Patterns in sign-form usage during the Old and Middle Kingdoms are discussed, and reasons for sign-form variation from the Old through New Kingdoms are suggested.